2009
DOI: 10.3928/1081597x-20091117-04
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Evaluation of an Intraocular Femtosecond Laser in Cataract Surgery

Abstract: Initial results with an intraocular femtosecond laser demonstrate higher precision of capsulorrhexis and reduced phacoemulsification power in porcine and human eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
328
3
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(365 citation statements)
references
References 36 publications
10
328
3
24
Order By: Relevance
“…[1][2][3][4]6 Regarding safety features of the FLACS, studies have shown that the incidence of intraoperative complications such as suction breaks or anterior capsular tears decreased with experience and were o2%. 1-3 Macular thickness did not differ between FLACS and traditional phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4]6 Regarding safety features of the FLACS, studies have shown that the incidence of intraoperative complications such as suction breaks or anterior capsular tears decreased with experience and were o2%. 1-3 Macular thickness did not differ between FLACS and traditional phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Macular thickness did not differ between FLACS and traditional phacoemulsification. [1][2][3] Additionally, the Femtosecond laser-assisted anterior capsulotomy was a safe procedure for postoperative posterior capsule opacification rates due to better intraocular lens position. 13 Table 1 Descriptive statistics (mean ± standard deviation, minimum, maximum, n = number) and P-value of different anterior chamber (AC) and cornea characteristics (AC depth, AC volume, AC angle, corneal thickness (CT), central corneal thickness (CCT), endothelial cell (CD)) in the complete study population according to three measuring times-preoperatively, 10 min post femtosecond laser treatment and 1 day follow up…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambrósio fez excelente revisão sobre este tipo de laser recentemente nesta revista (1) . A primeira facectomia em humanos assim realizada foi em 2008, na cidade de Budapeste (2) . Até o momento, já passam de dois mil casos operados em todo o mundo.…”
unclassified